Impacts of high precipitation on the energy and water budgets of a humid boreal forest - Isabelle, Pierre-Erik; Nadeau, Daniel F.; Anctil, François; Rousseau, Alain N.; Jutras, Sylvain; Music, Biljana (Agricultural and forest meteorology, 2020)
•Evapotranspiration (E) from a humid balsam fir boreal site was measured for 3 years.•Precipitation (P) and E from 13 boreal sites were compared to the study site.•Annual P ranged from 250 to 1600 mm, but annual E was capped to 550 mm at all sites.•Under the greatest annual P, the main study site hence had large annual runoff.•E could be limited by the canopy hydraulic transfer capacity or low energy inputs. The boreal forest will be strongly affected by climate change and in turn, these vast ecosystems may significantly impact global climatology and hydrology due to their exchanges of carbon and water with the atmosphere. It is now crucial to understand the intricate relationships between precipitation and evapotranspiration in these environments, particularly in less-studied locations characterized by a cold and humid climate. This study presents state-of-the-art measurements of energy and water budgets components over three years (2016–2018) at the Montmorency Forest, Québec, Canada: a balsam fir boreal forest that receives ∼1600 mm of precipitation annually (continental subarctic climate; Köppen classification subtype Dfc). Precipitation, evapotranspiration and potential evapotranspiration at the site are compared with observations from thirteen experimental sites around the world. These intercomparison sites (89 study-years) encompass various types of climate and vegetation (black spruces, jack pines, etc.) encountered in boreal forests worldwide. The Montmorency Forest stands out by receiving the largest amount of precipitation. Across all sites, water availability seems to be the principal evapotranspiration constraint, as precipitation tends to be more influential than potential evapotranspiration and other factors. This leads to the Montmorency Forest generating the largest amount of evapotranspiration, on average ∼550 mm y−1. This value appears to be an ecosystem maximum for evapotranspiration, which may be explained either by a physiological limit or a limited energy availability due to the presence of cloud cover. The Montmorency Forest water budget evacuates the precipitation excess mostly by watershed discharges, at an average rate of ∼1050 mm y−1, with peaks during the spring freshet. This behaviour, typical of mountainous headwater basins, necessarily influence downstream hydrological regimes to a large extent. This study provides a much needed insight in the hydrological regimes of a humid boreal-forested mountainous watershed, a type of basin rarely studied with precise energy and water budgets before.